2013
DOI: 10.1007/s10637-013-9959-2
|View full text |Cite
|
Sign up to set email alerts
|

Excessive MET signaling causes acquired resistance and addiction to MET inhibitors in the MKN45 gastric cancer cell line

Abstract: The clinical efficacy of MET tyrosine kinase inhibitors (MET-TKIs) is hindered by the emergence of acquired resistance, presenting an obstacle to drug discovery. To clarify the mechanisms underlying acquired resistance to MET-TKIs, we established resistance models by continuous exposure of the MET-amplified gastric cancer cell line MKN45 to MET-TKIs, PHA665752 (MKN45-PR) and GSK1363089 (MKN45-GR). Baseline expression and phosphorylation of MET were elevated in MKN45-PR and MKN45-GR compared to MKN45 cells, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 34 publications
3
19
0
Order By: Relevance
“…In those cell lines NPM-ALK overexpression was abrogated, consistently with data shown. Thus, in line with other cases of resistance, such as B-Raf, BCR-ABL, and others 31-34, 49 , our data suggest that patients that have developed resistance to ALK TKI mediated by NPM-ALK amplification might benefit from cycles of administration and suspension of TKI treatment, the so called “drug holiday” therapy (Fig.8) 50, 51 . Recently, a drug holiday approach for NPM-ALK amplified ALCL was also proposed by Amin et al with experiments in xenograft mouse models 28 .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In those cell lines NPM-ALK overexpression was abrogated, consistently with data shown. Thus, in line with other cases of resistance, such as B-Raf, BCR-ABL, and others 31-34, 49 , our data suggest that patients that have developed resistance to ALK TKI mediated by NPM-ALK amplification might benefit from cycles of administration and suspension of TKI treatment, the so called “drug holiday” therapy (Fig.8) 50, 51 . Recently, a drug holiday approach for NPM-ALK amplified ALCL was also proposed by Amin et al with experiments in xenograft mouse models 28 .…”
Section: Discussionsupporting
confidence: 82%
“…In another notable example, melanoma cells develop resistance to B-RAF inhibitors, and B-RAF TKI suspension in resistant cells induces cell toxicity mediated by an excess of B-RAF oncogenic signaling 32 . Similar observations have been described in a few other cancer models 33, 34 . Overall, these data indicate that an intermitting administration of a TKI could represent a therapeutic approach designed to overcome TKI resistance in different tumors.…”
Section: Introductionsupporting
confidence: 89%
“…TKI-resistance-conferring MET kinase domain mutations, including Y1248H and L1213V, have been identified in hereditary papillary renal cell carcinomas (14), and longterm exposure to MET TKI in vitro leads to acquisition of these mutations in MET-expressing gastric cancer cells (15,16). Such kinase-activating mutations are thought to interfere with ATP-competitive TKI binding, and they likely contribute to both primary and acquired drug resistance in MET-dependent cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, although crizotinib can inhibit the activity of most MET mutants, some constitutively active mutants, including MET-L1213V and -Y1248H, are resistant to this inhibitor (12,14). Additional studies have suggested that these mutations not only mediate primary resistance to MET inhibitors but may also play a role in acquired resistance to MET-TKI (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…C‐Met is the receptor tyrosine kinase encoded by proto‐oncogene and its amplification in numerous cancers has been demonstrated with high sensitivity to Met‐targeted therapy (Bahrami et al, ; Funakoshi et al, ; Pennacchietti et al, ). Yet, only a minority of patients respond to this therapy (innate resistance) and patients that initially show a dramatic response almost invariably relapse (acquired resistance) (De Palma & Hanahan, ; Funakoshi et al, ; Pennacchietti et al, ; Straussman et al, ). HGF, which is the sole known ligand to c‐Met, is most common produced by CAFs paracrine (Funakoshi et al, ; Pennacchietti et al, ).…”
Section: Mainly Signaling Pathway Activated By Cafsmentioning
confidence: 99%